MANAJEMEN LITERASI SEKOLAH DALAM MENUMBUHKAN MINAT BACA PESERTA DIDIK DI SMP NEGERI 02 BELITANG KABUPATEN OKU TIMUR - Zakiah Zakiah (Jurnal Manajemen Pendidikan, 2026)
Objective; This study aims to describe the implementation of school literacy management in fostering students' interest in reading and analyze the relationship between school literacy management and increased interest in reading at SMP Negeri 02 Belitang. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through interviews, observation, and documentation. Research informants consisted of the principal, teachers, literacy coordinators, librarians, and students from grades VII to IX who were selected using purposive sampling techniques. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions using the Miles and Huberman model. Data validity was obtained through source triangulation and technical triangulation. The results of the study indicate that school literacy management at SMP Negeri 02 Belitang is implemented through four management functions, namely planning, organizing, implementing, and evaluating. In the planning stage, the school developed a 15-minute reading program, provided a reading corner, and integrated literacy activities into the learning process. Organization was carried out through the formation of a literacy team with a clear division of tasks. The program implementation was effective and has become a school culture, marked by increased library visits and active student involvement. Program evaluations are conducted periodically using the CIPP model to ensure program sustainability.